Comparison of Post-Operative Range of Movement of Supra-Condylar Type 3 Fracture of Humerus in Children Operated by Medial and Posterior Approach - Rashid, Haroon; Mahmood, Khalid; khan, Shaukat Hayat; Arra, Iffat; Summyia, . (Biological and Clinical Sciences Research Journal, 2025)
Supracondylar fractures of the humerus are the most common elbow fractures in the pediatric population, often requiring surgical intervention when displaced. The choice of surgical approach can influence the functional and cosmetic outcomes, particularly the range of motion (ROM) post-operatively. Objective: To measure and compare the post-operative range of motion using two different approaches—medial and posterior—for open reduction and internal fixation of supracondylar humerus fractures in children. Methods: This quasi-experimental study was conducted at Sheikh Khalifa Bin Zayed/Combined Military Hospital (SKBZ/CMH), Muzaffarabad. After ethical approval, 250 pediatric patients with Gartland type-III supracondylar humerus fractures were included through random allocation into two groups: Group MA (medial approach) and Group PA (posterior approach). Open reduction and internal fixation were performed accordingly. The primary outcome was range of motion, classified as excellent, good, fair, or poor, while secondary outcomes included preservation of carrying angle and rate of complications. Data were analyzed using SPSS, and Chi-square test was applied to assess statistical significance. Results: In Group MA, 94 patients (76.4%) had excellent ROM, 25 (20.3%) had good ROM, and 4 (3.3%) had fair ROM. In Group PA, 76 patients (62.3%) achieved excellent ROM, 35 (28.7%) good, and 11 (9.0%) fair. The difference in ROM outcomes between the two groups was statistically significant (p < 0.05). Cosmetic outcomes corresponded closely with functional outcomes in both groups. Conclusion: The medial surgical approach for open reduction and internal fixation of type-III supracondylar humerus fractures in children is associated with significantly better post-operative range of motion compared to the posterior approach, with similar cosmetic outcomes and complication rates.